CLINICAL STUDY ON TE-031 TABLET IN DERMATOLOGY - KUMAKIRI, MASANOBU; OHKAWARA, AKIRA; YASUI, CHIKAKO (CHEMOTHERAPY, 1988)
We examined the usefulness of a new antibiotic, TE-031, in dermatology. Subjects had acne conglobata (2 cases), folliculitis (1), furuncle (2), impetigo eczematosa (1), subcutaneous abscess (1), and inflammatory atheroma (1). Improvement was moderate in 50% and slight in 50% of the patients. These results were acceptable, since the patients had underlying diseases or had been previously treated unsuccessfully. No side-effects or abnormal laboratory values were detected.